Direct Intentionalism and its Impact on the Recipient in Ma'rouf Al-Rusafi's Divan: A Pragmatic Study (Raparin Journal of Humanities (RJH), 2024)
This study, titled “Direct Intentionalism and its Impact on the Receiver in Divan Ma’ruf Al-Rusafi, a Pragmatic Study,” seeks to monitor direct intentionality and its impact on the recipient, through selected models, based on the fact that speech is not devoid of intentionality, which is one of the elements that contribute to directing the parties to the communicative process. Whether intentionality is direct or indirect, the research is limited to direct intentionality through: informative intentionality, presupposition intentionality, and direct verbal intentionality. The research tries to shed light on these deliberative mechanisms used by the poet to communicate his direct intention to the recipient in order to influence the recipient, and change his ideas and beliefs, and urge the recipient towards sophistication and progress and reject backwardness and isolation and ignorance.